Five essays on unionization and labour markets in Canada and the United States - Johnson, Susan (My University, 2001)
This thesis consists of five essays in the discipline of labour economics. The first essay uses cross-section time series analysis to estimate the impact of mandatory votes and card check on union certification success. The second examines the behaviour of Canadian union density from 1980 to 1998 and uses projections to look at the future of the Canadian union movement. The third investigates the decline of private sector U.S. union density from 1983 to 1999. The fourth essay considers the impact of three factors on the Canada-U.S. union density gap from 1980 to 1999: the difference in overall economic performance between the U.S. and Canada; structural change; and union recognition procedures. The fifth essay describes the behaviour of earnings per week, wages per hour and hours per week of prime-aged males by skill-group (identified by earnings quintile) in the U.S. and Canada from 1981 to 1997. This essay also provides evidence on relative downward wage rigidity in Canada.
Keywords: Labor Economics; Labor Economics